Investigation of low-level supergeostrophic wind and Ekman spiral as observed by a radar wind profiler in Beijing - Wang, Songqiu; Guo, Jianping; Xian, Tian; Li, Ning; Meng, Deli; Li, Hongjin; Cheng, Wei (Frontiers in Environmental Science, 2023)
The supergeostrophic flow remains seldomly reported from an observational perspective. Here, one year record of radar wind profiler measurements and ERA-5 reanalysis collected at Beijing observatory station are used to characterize the vertical structures of supergeostrophic wind and Ekman spirals in the lower troposphere. It is found that supergeostrophic flow shows significant diurnal variation, with lowest frequency for the supergeostrophic wind forming during daytime under clear-sky conditions, largely due to strong turbulent mixing and friction in the daytime. By comparison, the planetary boundary layer at night is stably stratified, the supergeostrophic wind occurs more frequently due to friction-induced decoupling from the ground surface. Furthermore, the presence of cloud makes the supergeostrophic wind occur more often in the daytime. Also, the geostrophic wind deviation within 1 km of atmosphere is found to be more negatively associated with the difference between surface temperature and 2-m air temperature compared with that in the altitude range of 1–3 km, indicating that the supergeostrophic wind near ground surface is more subject to the influence of heat flux. Intriguingly, most of the vertical wind profiles in the PBL are found not to follow Ekman spiral under neutral atmospheric conditions. The supergeostrophic winds contribute significantly to the magnitude of Ekman spirals in the upper mixed layer. Overall, the profiles and evolution features of the supergeostrophic wind and Ekman spirals observed in the lower troposphere in Beijing are much complicated than expected. The findings lay a solid foundation for better elucidating the low-level atmospheric dynamics in Beijing.